Perlindungan hukum terhadap korban tindak pidana penjambretan (Studi Putusan PN Medan Nomor: 3431/Pid.B/2020/PN.Mdn): perlindungan korban menurut hukum pidana Indonesia , perlindungan korban menurut Putusan Nomor 3431/Pid.B/2020/PN Mdn - ayu fazira (Faculty of Law Universitas Lancang Kuning, 2023)
There is a difference between mugging and theft in the way it is done. Mugging is taking by force (other people's things that are worn or carried. Mugging is part of a form of theft that uses violence, which not only results in material loss but also results in injury or can even result in the loss of the victim's life. The research method used is Normative juridical research. The results of the study show that victims still do not receive adequate protection, thus allowing victims to become repeated victims of both criminal acts and law enforcement or the criminal justice system.